Water profiling off Sarawak coastal areas - Manson, Ann Aletheia A (Universiti Malaysia Sarawak (UNIMAS), 2015)
During June 2009, Prime Scientific Sailing Expedition (EPSP) was carried out on South China Sea (SCS) along Sarawak waters. The physical properties of seawater were obtained using 'Conductivity-Temperature-Depth' (CTD) profiler. The main purpose of this present study is to construct vertical structures of temperature and salinity of Sarawak coastal waters, to construct temperature-salinity (T -S) diagram and identify the water masses, as well as to observe the features of Sarawak coastal waters. Vertical profiles of temperature, salinity and T-S diagrams were plotted and analyzed. Definitions of identified water masses in the Sarawak coastal were classified with respect to classification ofprevious studies done on SCS and redefined. Five water masses found exist in Sarawak water namely Continental Shelf Water (CSW), Open Sea Water (OSW), Maximum Salinity Water (MSW), Permanent Thermocline Water (PTW) and Water Mass 1 (WMI), derived from the mix of OSW and MSW. The definition of water mass is essential to understand better geographical positions of water mass to aid in the completion ofwater mass definitions done on SCS waters.